Marketing of pigs in Malaysia: an evaluation of market integration - Mohamed, Zainal Abidin; Mohd Arshad, Fatimah (Penerbit Universiti Kebangsaan Malaysia, 1996)
This paper examines the pricing efficiency of the pig market in Peninsular Malaysia through measuring the degree of market integration. Specifically, this paper examines the price linkages between Kuala Lumpur (which is considered the market centre for price discovery) and five major local markets (Ipoh, Johor Bahru, Penang, Malacca and Seremban). The findings indicate, with the exception of Johor Bahru, the other market regions show high level of market linkage with Kuala Lumpur.